The prevalence of enterhaemorrhagic escherichia coli in children presenting with diarrhoea at University of Benin Teaching Hospital, Benin, Nigeria - A I Omoigberale; M Okolie; M Ajieh (International Journal of Medicine and Health Development, 2002)
Objective: To determine the prevalence of enterohaemorrhagic Escherichia coli (EHEC), the pathogenicity of other strains of Escherichia coli and other organisms in children presenting with and without diarrhoea in the hospital. Subjects and Methods: A total of 247 stool samples collected from children aged 1 month to 7 years, made up of children with diarrlhoea (90) and children without diarrhoea (157), were screened for the presence of enterohaemorrhagic Escherichia coli (EHEC). Microscopy, culture and biochemical tests were done on all stool samples for the presence of EHEC and other enteric pathogens and for the presence of parasites. Results: Out of the 247 stools tested, 103 (41.7%) were infected with pathogenic organisms. No protozoan parasite was isolated. Out of the 90 children with diarrhoea and the 157 children without diarrhoea, 64 (71.1%) and 39 (24.8%) (X2 = 2.462; P<0.05) were infected with pathogenic organisms, respectively. The pathogenic organisms which included other strains of Escherichia coli which were not typed had the highest prevalence (87.4%) as against staphylococcus aureus (11.7%) and Candida species (0.9%). (X2 3.342; P<0.05). However No EHEC, shigellae and salmonella species were isolated. A moderately significant association was found between the ages of children and E coli. Infection, with children below 4 years of age, having the highest prevalence (X2 2.632, P< 0.05). There was an inverse relationship, the younger children had more pathogenic infections than the older children. No statistical significance was found between the sexes and E Coli infection (X2 =0.432; P>0.05) and also between the sources of water supply and E. coil infection (X2 = 0.502; P>0.05) Conclusion: This study which was specifically carried out to determine the prevalence of EHEC in diarrhoea children recorded a zero prevalence. However in the course of the study other strains of E. coli and other organisms were isolated as reported in the study. This suggests therefore that EHEC is not a common cause of watery diarrhoea in children. We suggest that further work be done using bloody stool samples and stool samples from children with renal failure. Perhaps its prevalence may be higher as EHEC is thought to be strongly associated with bloody diarrhoea and children with haemolytic uraemia syndrome.